RESPONSE OF COLOUR AND HYGROSCOPIC PROPERTIES OF SCOTS PINE WOOD TO ?HERMAL ?ODIFICATION - Kamperıdou, Vasiliki; Barboutıs, İoannis; Vasıleıou, Vasileios (Bartın Üniversitesi, 2012)
The effect of heat treatment on wood surface colour and hygroscopic properties of pine wood were investigated in this study. Boards of Scots pine wood (Pinus sylvestris L.) were subjected to thermal treatment at 200 °C, for 4, 6 and 8 hours. The change of equilibrium moisture content and density values of the specimens, due to the thermal treatment were recorded, in order to facilitate the understanding of the treated material behavior. The colour parameters L*, a* and b*, used to depict the total colour change (??) of wood surface, were proved to change proportionally to the treatment intensity. Moreover, the swelling in tangential and radial direction and the absorption of the specimens as well, appeared to be enhanced in great extent by the thermal treatment process. Mean value of Swelling percentage in tangential direction decreased 10.26%, 17.22% and 19.60% for specimens treated for 4, 6 and 8 hours, respectively, referring to the final measurement after 72 hours of immersion. In radial direction, mean value of Swelling percentage decreased 19.56%, 32.75% and 34.65% for treated for 4, 6 and 8 hours specimens, respectively, after 72 hours immersion, which attests the swelling decrease and the improvement of the hygroscopic behavior of Scots pine wood.

The effect of heat treatment on wood surface colour and hygroscopic properties of pine wood were investigated in this study. Boards of Scots pine wood (Pinus sylvestris L.) were subjected to thermal treatment at 200 °C, for 4, 6 and 8 hours. The change of equilibrium moisture content and density values of the specimens, due to the thermal treatment were recorded, in order to facilitate the understanding of the treated material behavior. The colour parameters L*, a* and b*, used to depict the total colour change (??) of wood surface, were proved to change proportionally to the treatment intensity. Moreover, the swelling in tangential and radial direction and the absorption of the specimens as well, appeared to be enhanced in great extent by the thermal treatment process. Mean value of Swelling percentage in tangential direction decreased 10.26%, 17.22% and 19.60% for specimens treated for 4, 6 and 8 hours, respectively, referring to the final measurement after 72 hours of immersion. In radial direction, mean value of Swelling percentage decreased 19.56%, 32.75% and 34.65% for treated for 4, 6 and 8 hours specimens, respectively, after 72 hours immersion, which attests the swelling decrease and the improvement of the hygroscopic behavior of Scots pine wood.
RESPONSE OF COLOUR AND HYGROSCOPIC PROPERTIES OF SCOTS PINE WOOD TO THERMAL MODIFICATION
Keywords: Biomaterial; Biyomateryaller